Assessment of psychosocial morbidity among medical interns during COVID-19 pandemic in Chennai district, Tamil Nadu – a cross-sectional study - Surya, B. N.; Radhakrishnan, Akshaya; Vijayalakshmi S; Narayanan, A. Hari; Kumar, S. Madhush; Venkatesh, B. N.; Syed, Rehana (Journal of Applied Pharmaceutical Research, 2024)
Background: Medical interns develop apprehensions about the vulnerability of their exposure to infection while treating COVID-19 patients, which may further affect their work patterns and efficiency. Studies have shown that the outbreak of infectious diseases would result in mental health issues. Because of this, our study aims to assess psychosocial factors such as anxiety, depression, stress, relationships with peers, and changes in personal roles among medical interns at a private medical college. Methodology: This cross-sectional was conducted among 248 medical interns using a simple random sampling method. Depression, anxiety, and stress were assessed using a standardized 21-item depression, anxiety, and stress questionnaire (DASS– 21). A pretested semi-structured questionnaire was used to acquire information regarding the study participants' socio-demographic data and social elements. Results: The overall prevalence of Depression [58%], Anxiety [70%], and Stress [44%] were found among the 248 study participants. Around [70.6%] of the study participants reported that their social life had been affected. The prevalence of various factors associated with depression, anxiety, and stress were assessed. Conclusion: This study reports higher levels of psychosocial distress among the study participants. Adequate knowledge about the pandemic and stress management measures will be the top priority among these budding medicos during such unfavorable pandemic situations.